Factors Associated with the Human Papillomavirus Vaccine Coverage in Gulu District, Uganda - Ojok, Isaac Odongo; Ogwal, John Baptist; Wwesige, Brian; Bongomin, Felix; Akello, Franceska (Adolescent Health, Medicine and Therapeutics, 2023)
Human papillomavirus (HPV) vaccination is an effective public health measure for the prevention of cancer of the cervix. We aimed to assess HPV vaccine coverage and associated factors in Gulu, Uganda. In October 2021, we conducted a cross-sectional study among girls aged 9 to 13 years residing in Pece-Laroo Division, Gulu City, Uganda. HPV vaccine coverage was defined as receipt of at least a dose of the HPV vaccine. A total of 197 girls, with a mean age of 11±1.4 years, were enrolled. Most participants were of the Acholi tribe (89.3%, n=176), catholic (58.4%, n=115), and in primary 5 level of education (36%, n=71). Overall, 68(35%) participants had received the HPV vaccine. Factors associated with HPV vaccine utilization were, good knowledge of the HPV vaccine (adjusted odds ratio (aOR) =0.233, 95% confidence interval (95CI): 0.037–0.640, p=0.101), methods of HPV prevention (OR=0.320, 95CI: 0.112–0.914, p = 0.033), good knowledge of the importance of HPV vaccination (OR=0.458, 95% CI: 0.334–0.960, p=0.021), knowledge on frequency of HPV vaccination (OR=0.423, 95CI:0.173–0.733, p=0.059), and good mobilization (OR=0.443, 95% CI: 0.023–0.923, p=0.012). In this community-based study, only one third of eligible girls received the HPV vaccine. Public health interventions are recommended exponentially to enhance the utilization of the HPV vaccine in this community.